Effect of Preoperative Embolization on the Intraoperative Bleeding during Posterior Stabilization in Thoracolumbal Fracture Cases at Prof. Dr. R. D Kandou Hospital Manado - Nathaniel Pali; Tommy Suharso; Richard Sumangkut; Billy Karundeng; Djony E. Tjandra; Yuansun Khosama; Windy M. V. Wariki (e-CliniC, 2023)
Abstract: Embolization is a technique to stop or prevent bleeding by inserting an object, such as an air-filled membrane (balloon), or an embolic material such as foam into a blood vessel to block the blood flow. This study aimed to prove that preoperative embolization might affect and reduce the amount of intraoperative bleeding during the posterior stabilization procedure for thoracolumbal vertebrae fracture. A quasi-experimental method was chosen for this study, and samples were not taken at random. Samples were patients with thoracolumbal vertebrae fracture who underwent the posterior stabilization procedure. Samples were divided into two groups, treated with and without preoperative embolization groups. The treatment was given 24-48 hours before posterior stabilization procedure. The intraoperative bleeding was measured in milliliters. The resulys showed that the average intraoperative blood loss was 283.3 mL, meanwhile of the untreated group was 583.3 mL. The one-way t-test resulted in a p-value of 0.004 at 5% of significance. In conclusion, preoperative embolization could reduce the amount of blood loss during intra-operative posterior stabilization in patients with thoracolumbar vertebral fractures. Further research on preoperative embolization in patient who will undergo posterior stabilization surgery of the thoracolumbal region due to fracture, either mechanically or generatively, is needed. Keywords: preoperative embolization; intraoperative blood loss